1997
DOI: 10.1007/s004390050455
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of the GSTM1 0/0 genotype in French heavy smokers with various types of chronic bronchitis

Abstract: A homozygous gene deletion of the glutathione S-transferase M1 (GSTM1) locus of genomic DNA from blood spots was studied by the polymerase chain reaction in a group of French heavy smokers (n = 361), which included patients with severe chronic bronchitis (SCB; n = 87), moderate chronic bronchitis (MCB: n = 102) and hard smokers (HS) with no permanent clinical symptoms of chronic bronchitis (n = 172). The GSTM1 0/0 genotype was found in 71.3% and 65.7% of cases in SCB and MCB, respectively, compared with only 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 14 publications
2
33
1
5
Order By: Relevance
“…Number of female smokers was very less, so it was not possible to compare the results between both the genders. No significant differences were observed between smokers and non-smokers, alcoholic and non-alcoholic individuals, tobacco chewers and non-chewers, carrying homozygous GSTM1/GSTT1/GSTM1T1 null genotype (p>0.05) ( Anantharaman, 2007;Buch et al, 2002;Nair et al, 1999 South Indians c 1744 485 (27.8)** 242 (13.9) 136 (7.8) Naveen et al, 2004;Samson, 2007;Shehnaz et al, 2011;Sreelekha et al, 2001;Suneetha, 2011;Vettriselvi et al, 2006;Vijayalakshmi et al, 2005 East Indians d 67 18(27.0) 9 (13.0) Sikdar et al, 2005 Central Indians e 282 99 (35.1) 37 (13.0) Devi et al, 2008 North Nair et al, 1999;Singh et al, 2009 Blacks b 3008 960 (31.9) 744 (24.9)* 298 (9.9)* Adams et al, 2003;Benzamin et al, 2011;Coutinho et al, 2010;Dandara et al, 2002;Lavender et al, 2009;Masimirembwa et al, 1998;Millikan et al, 2000;Rossini et al, 2002 Caucasians c 2674 1064/2232 (47.7)* 448/2674 (16.7) 31 (9.3) Amer et al, 2011;Baranova et al, 1997;Chen et al, 1996;D'Alo et al, 2004;Gsur et al, 2001;Kargas et al, 2003;Millikan et al, 2000;Mitrunen et al, 2001;Steinhoff et al, 2000;Welfare et al, 1999 Asians 1). The frequency distribution of GSTM1 and GSTT1 alleles were compared between different states of India and other populations all over the world (Table 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Number of female smokers was very less, so it was not possible to compare the results between both the genders. No significant differences were observed between smokers and non-smokers, alcoholic and non-alcoholic individuals, tobacco chewers and non-chewers, carrying homozygous GSTM1/GSTT1/GSTM1T1 null genotype (p>0.05) ( Anantharaman, 2007;Buch et al, 2002;Nair et al, 1999 South Indians c 1744 485 (27.8)** 242 (13.9) 136 (7.8) Naveen et al, 2004;Samson, 2007;Shehnaz et al, 2011;Sreelekha et al, 2001;Suneetha, 2011;Vettriselvi et al, 2006;Vijayalakshmi et al, 2005 East Indians d 67 18(27.0) 9 (13.0) Sikdar et al, 2005 Central Indians e 282 99 (35.1) 37 (13.0) Devi et al, 2008 North Nair et al, 1999;Singh et al, 2009 Blacks b 3008 960 (31.9) 744 (24.9)* 298 (9.9)* Adams et al, 2003;Benzamin et al, 2011;Coutinho et al, 2010;Dandara et al, 2002;Lavender et al, 2009;Masimirembwa et al, 1998;Millikan et al, 2000;Rossini et al, 2002 Caucasians c 2674 1064/2232 (47.7)* 448/2674 (16.7) 31 (9.3) Amer et al, 2011;Baranova et al, 1997;Chen et al, 1996;D'Alo et al, 2004;Gsur et al, 2001;Kargas et al, 2003;Millikan et al, 2000;Mitrunen et al, 2001;Steinhoff et al, 2000;Welfare et al, 1999 Asians 1). The frequency distribution of GSTM1 and GSTT1 alleles were compared between different states of India and other populations all over the world (Table 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…reported first that EPHX1 gene polymorphisms were associated with susceptibility to pulmonary emphysema. There has been also some evidence that GSTM1 null genotype might be related to severe bronchitis in heavy smokers [20] and to reduction in lung function and emphysema in smokers with bronchogenic carcinoma [19,37]. Moreover, DeMeo and co-authors reported an association of GSTP1 and EPHX1 gene polymorphisms with emphysema distribution [38].…”
Section: Discussionmentioning
confidence: 99%
“…The GSTP1 105Ile/Val substitution is located near the substrate-binding site, leading to a different enzyme activity depending on the type of chemical reaction [18]. These GST polymorphisms have been investigated in relation to COPD, but without definitive conclusions [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that endometriosis is inherited as a complex genetic trait, implying that multiple gene loci interact with both each other and the environment to produce the phenotype disease (Kennedy 1997). Recent genetic studies have found an association between the development of endometriosis and the polymorphisms of several genes (Cramer et al 1996;Baranova et al 1997;Watanabe et al 2001;Chang et al 2002;Wieser et al 2002;Hur et al 2005), including the genes related to estrogen metabolism (Georgiou et al 1999;Kitawaki et al 2001;Kado et al 2002).…”
Section: Introductionmentioning
confidence: 99%